PENDEKATAN TERPADU MENGGUNAKAN METODE QFD-ANP DALAM MENENTUKAN SASARAN PENINGKATAN RANCANGAN PADA PRODUK SPRINGBED - Sadikin Halim; Khawarita Siregar; Rosnani Ginting (Jurnal Teknik Industri USU, 2014)
Design is a form of plan, which can be proposals, drawings, models, or descriptions in order to produce an object, system, component, or structure. Designing is the first step in the manufacture of the product. Springbed is one type of bed that is widely used by the public, especially the middle class and above. Consumer needs continue to increase so that the required design new products that can meet the dynamic needs of consumers at PT. XYZ which springbed product’s sales decreased by 10 %. This study is intended to determined quality desain product according to consumer needs. Quality Function Deployment (QFD) is a method which translates customer needs to technical characteristics that can be intervened by the company. The relation of customer needs and technical characteristics is clarified by using Analytic Network Process (ANP). QFD-ANP method used to get a clear picture of the needs of consumers and more objective so as to look for factors that need to be repaired or upgraded. QFD-ANP approach result show that the technical characteristics of the mattress’s thickness, the size of the coils/spring, mattress’s brightness color are important technical characteristics to be improved with the degree of importance respectively 23,83 % , 23,42 % , and 20,33 % .